ADAPTIVE TRACKING OF MULTIPLE MANOEUVRING TARGETS IN CLUTTER USING THE IMM AND THE JPDAF (Sciences & Technologie. B, Sciences de l'ingénieur, 2003)
An algorithm for tracking multiple manoeuvring targets in a cluttered environment is proposed. This algorithm combines the Joint Probability Data Association Filter (JPDAF) and the interacting Multiple Model (IMM) algorithm and uses an adaptive update time. A  modified  version  of  the Van Keuk  method has been used to adaptively calculate the update time in the resulting  algorithm, called the Adaptive IMMJPDAF (AIMMJPDAF). The performance of the proposed algorithm is assessed via Monte Carlo simulation and compared to that of the adaptive IMMJPDAF that uses the original Van Keuk method and the IMMJPDAF that uses a constant update time.